Carbonate microfacies and chemostratigraphy of a late Aptian-early Albian marine distal section from the primitive South Atlantic (SE Brazilian continental margin): Record of global ocean-climate changes? - Caetano-Filho, Sergio [UNESP] (2017)
Late Aptian-early Albian limestones from the eastern Brazilian continental margin record the early evolution of the South Atlantic Ocean. In Tethyan and North Atlantic domains, a planktic foraminiferal turnover and organic-rich deposits related to Oceanic Anoxic Event lb (OAE lb) point to major ocean climate changes through this interval. Coeval organic-rich deposits of the South Atlantic Ocean have been interpreted as the product of restricted circulation rather than attributed to a global event. However, previous investigations of the early marine phase of South Atlantic lack data from more distal facies, making correlations to global events difficult. Here, we present C, O, and Sr isotopes, elemental geochemistry, TOC and pyrolysis data, as well as a microfacies analysis of an upper Aptian-lower Albian distal section from the Campos Basin (southeastern Brazil). Our focus is on the paleoenvironmental characterization of and the possible association between organic-rich deposits and major perturbations related to Aptian-Albian transition. Five microfacies associations (MA) were identified in the informal units I and III, which were deposited in the neritic region on a carbonate ramp. Organic-rich deposits were described in unit III, composed of planktic-dominated wackestones interbedded with black shales, in a distal dysoxic to anoxic environment. The carbonates Sr-87/Sr-86 ratios showed a drastic increase (0.7072-0.7074), interpreted as enhanced chemical weathering, supported by the increase of continental input to the top of section. This trend was accompanied by a long-term delta C-13(carb) negative excursion, which were assigned to the latest late Aptian-early Albian interval of the isotope reference curves, in accordance with the described occurrence of Colomiella recta. This scenario matches those proposed for the late Aptian-early Albian transition and OAE lb set, as an enhanced greenhouse stage, pointing to the influence of the referred ocean-climate changes on the deposition of organic-rich deposits of the early South Atlantic Ocean. This investigation gives more evidences that these perturbations were a widespread event, as a product of broad-scale disturbances in the global carbon cycle which also controlled organic deposition and preservation on restricted settings. (C) 2017 Elsevier Ltd. All rights reserved.